The Return of the Edwardians in Contemporary Fiction - Cruz-Rus, Celia (My University, 2016)
My research stems from the hypothesis that a subgenre exists within the contemporary historical novel in English with a series of features that can be labelled as neoEdwardian and belong in a broader social and cultural phenomenon. Thus, trough the analysis of a series of recent novels set in the years prior to the First World War, this dissertation could contribute to the study of the relationship that we establish with the past, especially when History and fiction interact in novels. The main goals of this research are: 1. To delve into the state of the art of contemporary historical fiction in English. 2. To trace the state of the art of the neo-Edwardian novel, including a chronology of primary works and their evolution. 3. To analyse a series of primary works that could be considered neo-Edwardian and to obtain some common features. 4. To investigate critical concepts about our contemporary views on the past that can be related to this subgenre. 5. To contribute to the study of the neo-historical novel. In order to achieve this, a thorough examination of a selection of contemporary novels set in the Edwardian period is being carried out. The theoretical framework employed revolves around memory in contemporary fiction and the evolution of the historical novel in the 20th and the 21st centuries.
Keywords: Literatura inglesa - S. XX; Neo-Edwardianism